2001
DOI: 10.1074/jbc.m007902200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis of Type III Antifreeze Protein Intramolecular Dimer

Abstract: The structure of a new antifreeze protein (AFP) variant, RD3, from antarctic eel pout (Rhigophila dearborni) with enhanced activity has been determined for the first time by nuclear magnetic resonance spectroscopy. RD3 comprises a unique translational topology of two homologous type III AFP globular domains, each containing one flat, ice binding plane. The ice binding plane of the N domain is located ϳ3.5 Å "behind" that of the C domain. The two ice binding planes are located laterally with an angle of 32 ؎ 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
67
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 31 publications
4
67
2
Order By: Relevance
“…One isoform (designated RD3) from the Antarctic eel pout (Lycodichthys dearborni) has two type III AFPs joined in tandem by a nine-amino acid linker peptide (23). This duplicated AFP with two similar AFP domains has been referred to in the literature as an intramolecular dimer (24) although there is no suggestion that the tandemly repeated AFPs contact each other. NMR analysis of the 14.7-kDa RD3 isoform indicates that the linker region is fairly flexible and may allow both ice-binding faces to engage the ice surface at the same time (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One isoform (designated RD3) from the Antarctic eel pout (Lycodichthys dearborni) has two type III AFPs joined in tandem by a nine-amino acid linker peptide (23). This duplicated AFP with two similar AFP domains has been referred to in the literature as an intramolecular dimer (24) although there is no suggestion that the tandemly repeated AFPs contact each other. NMR analysis of the 14.7-kDa RD3 isoform indicates that the linker region is fairly flexible and may allow both ice-binding faces to engage the ice surface at the same time (24).…”
mentioning
confidence: 99%
“…This duplicated AFP with two similar AFP domains has been referred to in the literature as an intramolecular dimer (24) although there is no suggestion that the tandemly repeated AFPs contact each other. NMR analysis of the 14.7-kDa RD3 isoform indicates that the linker region is fairly flexible and may allow both ice-binding faces to engage the ice surface at the same time (24). RD3 was reported to have twice the molar activity of the monomeric isoforms RD1 and RD2 (23) and anywhere from 1.5 to six times the activity of the recombinant N-terminal domain alone depending on the concentration tested (24).…”
mentioning
confidence: 99%
“…The currently available structural database for AFPIII includes NMR structures (Sönnichsen et al 1996;Miura et al 2001), X-ray structures (Graether et al 1999;Antson et al 2001), and a neutron structure (Howard et al 2011). On the basis of these data, Howard et al identified an ice-like geometry for four of the water molecules bound to a pocket of the IBS formed by Gln 9 , Thr 18 , Val 20 , and Met 21 , for which the anchoring role that leads to the AFP-ice interaction was assumed.…”
mentioning
confidence: 99%
“…Experimental accounts report that the binding of fish AFP to hexagonal pyramids is indexed frequently as (201) (14,16,17,19,21,23); but more elongated pyramids with higher indices such as (301) or (401) (24,25) and even extremely elongated pyramids with indices (501) or higher (15) have been reported. Less elongated pyramids with indices in the range (102)-(201), although not excluding the occurrence of (101), have also been observed (26,27) as well as combinations of such pyramids with the basal face (001) and various prisms (hk0) (17).…”
mentioning
confidence: 99%
“…The appearance of pyramidal forms on ice crystals grown under the influence of the AFP has thus far been explained (2,14,35) as the occurrence of an intermediate orientation between the basal face and the primary prism. For example, it is held in Refs.…”
mentioning
confidence: 99%